Interdependence between human capital and the power of a shadow economy: Lithuanian case study - Čiutienė, Rūta; Meilienė, Evelina; Savanevičienė, Asta; Vaitkevičius, Sigitas (Technological and Economic Development of Economy, 2015)
According to economic theory, economic growth is related to Human Capital (HC). Lithuania is associated with countries where a high level of shadow economy exists. This paper examines the issues of human capital development under conditions of shadow economy. The aim of this paper is to evaluate the power and effects of the Lithuanian shadow economy in the context of human capital and to assess the inter-dependence between the power of the shadow economy and human capital. The theoretical justification for research on the inter-dependence between the power of the shadow economy and human capital is based on the analysis of how changes in the human capital structure and indicators reflect the power of the shadow economy and vice versa. Theoretical analysis has been made on the main features and factors of shadow economy and possible tools of human capital evaluation. On the basis of theoretical findings, the model of shadow economy power has been created and using the linear regression method, the dependence of shadow economy power on human capital has been evaluated. The power of the shadow economy has been calculated as a function of population, GDP, trade, unemployment and the labor force. Variables of social development, such as demographic changes and risk of poverty, indicators of HC economic development and indicators of HC economic potential have been used for the research. For the evaluation of the interdependence of the variables, the years 2005–2012 were used. In evaluating human capital under the conditions of the shadow economy, a few periods have been identified and distinguished. Firstly, the results showed that the level of human capital education and unemployment can be described as the most important indicators that reflect the economic environment and shadow economy. Secondly, the increasing level of the shadow economy increases shadow unemployment, and this in turn influences the attraction of direct foreign investment. And finally, research on the influence of separate factors of the shadow economy on variables of human capital could disclose a deeper understanding of the impact of the shadow economy on human capital.